2019
DOI: 10.5144/0256-4947.2019.302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Baska and I-gel supraglottic airway devices: a randomized controlled study

Abstract: BACKGROUND: Laryngeal masks are increasingly used in place of endotracheal intubation or face masks for maintaining the airway during surgery.OBJECTIVES: Compare the insertion time and other features of the Baska and I-gel masks in patients undergoing general anesthesia for urological surgery.DESIGN: Randomized-controlled, single-blind study.SETTINGS: Urology surgical operating rooms of a tertiary care hospital.SUBJECTS AND METHODS: We enrolled concomitant patients whose surgery was expected to last less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…in their study comparing Baska mask ® and I-gel™ where the median time taken for device insertion in I-gel™ group was less compared to Baska mask ® group ( P < 0.05). [ 20 21 ] The reason for this is that I-gel™ is less bulky, easy to handle, bears high stability, and becomes immediately operational after insertion as having preformed non-inflatable cuff.…”
Section: Discussionmentioning
confidence: 99%
“…in their study comparing Baska mask ® and I-gel™ where the median time taken for device insertion in I-gel™ group was less compared to Baska mask ® group ( P < 0.05). [ 20 21 ] The reason for this is that I-gel™ is less bulky, easy to handle, bears high stability, and becomes immediately operational after insertion as having preformed non-inflatable cuff.…”
Section: Discussionmentioning
confidence: 99%
“…However, other parameters, such as insertion time, fibre-optic view of the glottis, the use of airway manipulation, heart rate, mean arterial pressure, PAP, lung compliance, and perioperative complications, were comparable [14]. A study by Kara et al showed that the Baska mask provided a significantly higher PAP than the i-gel (15.8 cm H 2 O ± 0.9 cm H 2 O and 14.9 cm H 2 O ± 1.7 cm H 2 O, respectively) [11], which was supported by our study. Even though our results showed that the i-gel was superior in some of the parameters, the margin of difference was actually not large.…”
Section: Discussionmentioning
confidence: 95%
“…Kara et al conducted a comparison study between the Baska mask and i-gel in 200 patients undergoing urologic surgery. The i-gel showed significantly shorter median insertion time than the Baska mask (7 s [5][6][7][8][9][10][11][12] and 14 s [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], respectively). However, there were no significant differences in the other parameters (the number of device placement attempts, sealed pressure and the number of post-operative complications) [11].…”
Section: Discussionmentioning
confidence: 99%
“…4 Insertion time of the Baska mask took 14 s in our study which was identical to previous literature that found 14-16 s insertion times for the Baska mask. 1,[5][6][7][8] Some other studies showed 21-24 s insertion times for the Baska mask. [9][10][11] This demonstrates that Baska mask insertion times can vary quite a bit.…”
Section: Discussionmentioning
confidence: 97%